Sentiment and returns: Analysis of investor sentiment in the South African market - Dalika, Naeem K (My University, 2014)
Modern financial theory generally has no room for investor sentiment. The standard argument is that in highly competitive financial markets, suboptimal trading behaviour such as paying attention to sentiment signals unrelated to fundamental value will be eliminated quickly by aggressive arbitrageurs. However, research in recent years illustrates that investor sentiment has a significant impact on the cross section of stock returns. This study contributes to the debate by examining the relationship between investor sentiment and stock returns in the South African Market. Theory predicts that a broad wave of sentiment will disproportionately affect stocks whose valuations are highly subjective and are difficult to arbitrage. To test this prediction we construct an aggregate measure of investor sentiment from several proxies and study the impact that it has on stock returns. The results indicate that investor sentiment has a strong impact on share returns in South Africa. When sentiment is low, subsequent returns are relatively high on smaller stocks, high volatility stocks, extreme growth stocks, and young stocks. When sentiment is high, on the other hand, these patterns fully reverse.